Helium ions at the heidelberg ion beam therapy center: comparisons between FLUKA Monte Carlo code predictions and dosimetric measurements. (1st August 2017) - Tessonnier, T; Mairani, A; Brons, S; Sala, P; Cerutti, F; Ferrari, A; Haberer, T; Debus, J; Parodi, K
Abstract: In the field of particle therapy helium ion beams could offer an alternative for radiotherapy treatments, owing to their interesting physical and biological properties intermediate between protons and carbon ions. We present in this work the comparisons and validations of the Monte Carlo FLUKA code against in-depth dosimetric measurements acquired at the Heidelberg Ion Beam Therapy Center (HIT). Depth dose distributions in water with and without ripple filter, lateral profiles at different depths in water and a spread-out Bragg peak were investigated. After experimentally-driven tuning of the less known initial beam characteristics in vacuum (beam lateral size and momentum spread) and simulation parameters (water ionization potential), comparisons of depth dose distributions were performed between simulations and measurements, which showed overall good agreement with range differences below 0.1 mm and dose-weighted average dose-differences below 2.3% throughout the entire energy range. Comparisons of lateral dose profiles showed differences in full-width-half-maximum lower than 0.7 mm. Measurements of the spread-out Bragg peak indicated differences with simulations below 1% in the high dose regions and 3% in all other regions, with a range difference less than 0.5 mm. Despite the promising results, some discrepancies between simulations and measurements were observed, particularly at high energies. These differences were attributed to an underestimation of dose contributions from secondary particles at large angles, as seen in a triple Gaussian parametrization of the lateral profiles along the depth. However, the results allowed us to validate FLUKA simulations against measurements, confirming its suitability for 4 He ion beam modeling in preparation of clinical establishment at HIT. Future activities building on this work will include treatment plan comparisons using validated biological models between proton and helium ions, either within a Monte Carlo treatment planning engine based on the same FLUKA code, or an independent analytical planning system fed with a validated database of inputs calculated with FLUKA.